VD_FINDINFO AM 46/17 - 52/2017 vom 21. Dezember 2017 - VD Tribunal cantonal (2017)
PRIME D'ASSURANCE-MALADIE, PAIEMENT, SUBVENTION, POURSUITE POUR DETTES, MAINLEVÉELP, DOMICILE EN SUISSE | 5 LAMal, 64a LAMal, 65 LAMal, 105a OAMal, 105b OAMal